2021
DOI: 10.1016/j.heliyon.2021.e06497
|View full text |Cite
|
Sign up to set email alerts
|

Geophagic practice in Mashau Village, Limpopo Province, South Africa

Abstract: Large quantities of earth materials are consumed daily in Mashau Village; nonetheless, this practice had not been studied. Furthermore, the motivations for this geophagic behaviour in the study area were unclear. Thus, questionnaires were distributed to 200 participants in the study area with the aim of generating data on the motivations of and potential medical conditions associated to this practice. About 91% of the participants were geophagists, of which 98.5% were female. Craving was found to be the main r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Finally, we need to answer the question of whether humans can practice geophagy safely, in cases where the practice cannot be discontinued (refer to the merits of processing the material before consumption, such as drying, baking, smoking and salting it). In urban areas in particular, health education ( 138 ) should also explain where unpolluted soils can be found, and which areas should be avoided.…”
Section: Suggested Areas For Further Researchmentioning
confidence: 99%
“…Finally, we need to answer the question of whether humans can practice geophagy safely, in cases where the practice cannot be discontinued (refer to the merits of processing the material before consumption, such as drying, baking, smoking and salting it). In urban areas in particular, health education ( 138 ) should also explain where unpolluted soils can be found, and which areas should be avoided.…”
Section: Suggested Areas For Further Researchmentioning
confidence: 99%
“…Kaolin-eating is common in the rural South of the United States, parts of Latin America, Asia and the Middle East ( 9 , 25 , 26 ). It is also common in Sub-Saharan Africa where several cultures especially farmers and nomad settings consume dirt, mainly clay ( 5 , 27 , 28 ) and in Australia during food scarcity ( 29 ). In most cases the habit is common amongst pregnant women.…”
Section: Prevalence Etiology and Management Of Geophagymentioning
confidence: 99%
“…Studies in Kenya ( 4 ) have confirmed these results, with children being the most exposed to geohelminths and trichuriasis ( 27 , 46 ). Also, incidences of death have been known to occur after the excessive consumption of some clay often due to intestinal occlusion or perforation ( 5 , 22 ).…”
Section: Prevalence Etiology and Management Of Geophagymentioning
confidence: 99%
See 1 more Smart Citation
“…This pathological craving and eating of items that are non-nutritive can be harmful to the child and could lead to legal suites against speech therapists and educationists. It is usually unnoticed and under reported ( Mashao et al, 2021). In absence of treatment it could lead to life threatening obesity.…”
Section: Picamentioning
confidence: 99%